Exploring The Influence of Electrode Material on Electrical Impedance Spectroscopy: A Comparative Analysis - Ahmad Zarkasi; Mohammad Asrul; Kholis Nurhanafi; Rahmawati Munir; Amirin Kusmiran; Kormil Saputra (Tinta Emas Publisher, 2024)
Electrodes play a crucial role in impedance measurements using the EIS method. This study undertook a comparative analysis of impedance measurement outcomes using aluminum, iron, stainless steel, copper, and tin electrodes with mineral water and distilled water as the measurement objects. The impedance Bode plots for mineral water and distilled water showed similar trends across all electrodes, while the phase difference trends varied. In this experiment, copper electrodes emerge as the preferred choice due to their consistently low impedance, particularly at higher frequencies, and their stable phase difference patterns. Additionally, copper electrodes showed superior stability up to 25 kHz, while tin electrodes remained stable up to 50 kHz, albeit valid only from a frequency of 100 Hz. The varying impedance and phase difference in mineral water measurements align with the Warburg impedance circuit, due to the presence of more complex capacitive and inductive elements. Furthermore, measurements with distilled water showed a uniform Bode plot pattern of both impedance and phase difference across all electrodes, making the Randles circuit approach the most appropriate choice in this case. Overall, all electrode types exhibited distinct characteristics.